Kepemimpinan transformasional dan instruksional kepala sekolah untuk meningkatkan mutu lulusan (studi kasus di SMA Muhammadiyah 1 Yogyakarta) - Primasary, Amalia; Syamsudin, Syamsudin (Indonesian Journal of Educational Management and Leadership, 2023)
This research aimed at (1) analyzing the transformational leadership of the principal to increase the quality of the graduates, (2) analyzing the instructional leadership of the principal to increase the quality of the graduates, and (3) analyzing the quality objectives of the graduates in SMA Muhammadiyah I Yogyakarta. This research used descriptive qualitative method with case study approach. The location of the research was in SMA Muhammadiyah I Yogyakarta. The respondents consist of the principal, the vice principal in charge of curriculum, and the teachers of SMA Muhammadiyah I Yogyakarta. The data collection techniques were with observation, interview, and documentation. The data analysis technique used data reduction, data presentation, and conclusion drawing. The research result showed that: (1) The transformational leadership of the principal of SMA Muhammadiyah I Yogyakarta has already been good in increasing the quality of the graduates, (2) The instructional leadership of the principal in increasing the quality of the graduates in SMA Muhammadiyah I Yogyakarta has already been good, and (3) the graduates of SMA Muhammadiyah Yogyakarta I were targeted to be accepted in their favorite universities. Because the fighting spirit of the students were relatively not high, the target was not entirely achieved. However, globally, the quality of the graduates at SMA Muhammadiyah I Yogyakarta has already been good.